TANGGUNG JAWAB KEPERDATAAN RUMAH SAKIT TERHADAP TINDAKAN DOKTER YANG DILAKUKAN DI BAWAH STANDAR PELAYANAN KEDOKTERAN DI KOTA BATAM - Aldo B.Wira Hatta; Alfis Setyawan (Fakultas Hukum, Universitas Internasional Batam, 2019)
The scientific research that the author did, aims to analyze how the legal relationship between doctors and hospitals in carrying out medical practices and the responsibility of the Civil Hospital for the actions of Doctors who practice under the Medical Service Standards. The research methodology that author use is the type of normative and empirical legal research, as the author uses the primary data that the author gets through interviews with several hospitals in Batam City and several doctors and secondary data obtained from library references. The results of the research that I have obtained from the interview method and literature study regarding the legal relationship that exists between the Hospital and the Doctor can be a work relationship or partnership relationship. Against these health services, it is not uncommon to find obstacles faced by hospitals and doctors, especially those operating in the city of Batam. The obstacle is in the form of a claim for compensation suffered by the patient for the action of the Doctor in providing services to patients under the standard of medical services. Against the civil lawsuit filed by the patient raises civil responsibility for the doctor who can also involve the Hospital to take responsibility for the doctor's actions based on Article 1367 of the Civil Code as well as Article 46 of Law Number 44 of 2009 concerning Hospitals, related to the legal responsibility of the hospital for losses incurred for negligence carried out by health workers at the Hospital. Thus a medical dispute arose which doctors had to face as well as the Hospital